Diabetes Is Associated with Musculoskeletal Pain, Osteoarthritis, Osteoporosis, and Rheumatoid Arthritis - Thomas Rehling; Anne-Sofie Dam Bjørkman; Marie Borring Andersen; Ola Ekholm; Stig Molsted (Journal of Diabetes Research)
Aim. To investigate the associations between diabetes and musculoskeletal pain, osteoarthritis, osteoporosis, and rheumatoid arthritis. Methods. Self-reported data were provided by the nationwide Danish National Health Survey 2013. Inclusion criteria were age≥40 years and known diabetes status. The exposure variable was diabetes, and the outcome variables included musculoskeletal pain during the last 14 days in three body sites (back/lower back, limbs, and shoulder/neck), osteoarthritis, osteoporosis, and rheumatoid arthritis. Logistic regression analyses adjusted for age, gender, BMI, education, marital status, and physical activity were performed. Results. 9,238 participants with diabetes were 65.6±11.0 (mean±SD) years old; 55.6% were males. 99,980 participants without diabetes were 59.2±11.8 years old; 46.7% were males. Diabetes was associated with back/lower back pain (OR 1.2 (CI 95% 1.1-1.2), p<0.001), pain in the limbs (1.4 (1.3-1.4), p<0.001), shoulder/neck pain (1.2 (1.1-1.3), p<0.001), osteoarthritis (1.3 (1.2-1.4), p<0.001), osteoporosis (1.2 (1.1-1.4), p=0.010), and rheumatoid arthritis (1.6 (1.4-1.7), p<0.001). In participants with diabetes, physical activity was associated with reduced pain (e.g., back/lower back pain (0.7 (0.6-0.7), p<0.001)). Conclusion. Diabetes was associated with elevated odds of having musculoskeletal pain. Diabetes was also associated with elevated odds of having osteoarthritis, osteoporosis, and rheumatoid arthritis. The most frequent disease in individuals with diabetes was osteoarthritis. The reported pain may have negative impacts on the level of physical activity. Health-care professionals should remember to inform patients with diabetes that musculoskeletal pain, osteoarthritis, osteoporosis, and rheumatoid arthritis are not contraindications to exercise training.